VERNONIA CINEREA (NEICHITTI KEERAI) REGENERATES PROXIMAL TUBULES IN CISPLATININDUCED RENAL DAMAGE IN MICE - Amuthan, Arul; Devi, Vasudha; Shreedhara, Chandrashekara Shastry; Rao, Venkata; Puri, Kunal; Jasphin, Shiny (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The aim of the study was to evaluate whether Vernonia cinerea (VC) regenerates the proximal renal tubular cells in cisplatin-induced necrosis in male Swiss albino mice. Methods: The crude aqueous extract (CAE) of VC was fractionated from non-polar to polar using different solvents. Mice were injected a single dose of cisplatin (15 mg/kg) on day 1, which took 5 days to cause maximal renal damage. From day 6, CAE and all fractions were orally administered (200, 300, and 400 mg/kg) for 5 continuous days. On day 11, blood was collected to estimate urea and creatinine. Kidney was collected for histology and grading was done. Results: Cisplatin induced proximal renal tubular damage (grade 5) in corticomedullary junction, characterized by necrosis, proximal tubular dilatation, inflammation and vasodilation. Aqueous fraction (AF) did not show any regeneration; whereas, 400 mg/kg dose of CAE and butanol fraction (BF) showed a significant reduction (p<0.001) in proximal tubular damage (Grade 3) and 50–75% regeneration of proximal tubular epithelial cells. Conclusion: This is the first study to demonstrate the regenerative potential of Neichitti kashayam (CAE of VC) and its BF in cisplatin-induced proximal tubular damage in kidney. Further study is warranted to find out the dose regimen for complete regeneration, lead compounds, and molecular mechanism.